The PI3K/Akt/mTOR signaling pathway plays a role in regulating aconitine-induced autophagy in mouse liver - Yang, Hanqi; Wang, Hui; Liu, Yanbing; Yang, Lin; Sun, Lu; Tian, Yanan; Zhao, Baoyu; Lu, Hao (Research in veterinary science, 2019)
Aconitine, a major aconitum alkaloid, is well known for its high toxicity that induces severe arrhythmias and neurological symptoms. One mechanism of aconitine-induced toxic responses is the induction of apoptosis. Apoptosis and autophagy are interconnected processes and the two pathways share critical components. In this study, we investigated the role of autophagy in aconitine-induced toxicity using mouse model. 120 mice were randomly divided into 4 experimental groups (normal saline), low dose group (0.14 μmol/L), medium dose group (0.28 μmol/L) and high dose group (0.56 μmol/ L). 30 mice in each group were administered with aconitine (lavage) for 30 days. The livers were collected for analysis of autophagy-related proteins by Western blotting. The expression of LC3II/LC3I ratio and Beclin 1 were found to increase and then decrease with the highest expression at 10 days and the p62 showed a time-dependent decreases. Autophagy is regulated by the mTOR pathway, we further analyzed the effects of aconitine on this pathway and found aconitine inhibited, phosphorylation of p-PI3K, p-Akt and p-mTOR. The p-p70s6k and p-4EBP1 which are downstream of mTOR were concomitantly decreased. These results suggest that aconitine induce autophagy in mouse liver. The PI3K/Akt/mTOR signaling pathway is involved in the regulation of aconitine-induced autophagy in the liver of mice. •Aconitine induced autophagy in the liver of mice in a time and dose dependent manner.•In the early stage of toxic responses the autophagy was activated thus functioning as a protective mechanism.•The PI3K/Akt/mTOR signaling pathway is involved in the regulation of aconitine-induced autophagy in the liver of mice.